Analysis benefits of a second Allo-HSCT after CAR-T cell therapy in patients with relapsed/refractory B-cell acute lymphoblastic leukemia who relapsed after transplant - Cao, Xing-yu; Zhang, Jian-ping; Zhao, Yan-li; Xiong, Min; Zhou, Jia-rui; Lu, Yue; Sun, Rui-juan; Wei, Zhi-jie; Liu, De-yan; Zhang, Xian; Yang, Jun-fang; Lu, Peihua (Frontiers in Immunology, 2023)
Background: Chimeric antigen receptor (CAR) T-cell therapy has demonstrated high initial complete remission (CR) rates in B-cell acute lymphoblastic leukemia (B-ALL) patients, including those who relapsed after transplant. However, the duration of remission requires improvements. Whether bridging to a second allogeneic hematopoietic stem cell transplant (allo-HSCT) after CAR-T therapy can improve long-term survival remains controversial. We retrospectively analyzed long-term follow-up data of B-ALL patients who relapsed post-transplant and received CAR-T therapy followed by consolidation second allo-HSCT to investigate whether such a treatment sequence could improve long-term survival. Methods: A single-center, retrospective study was performed between October 2017 and March 2022, involving 95 patients who received a consolidation second transplant after achieving CR from CAR-T therapy. Results: The median age of patients was 21.2 years (range: 2.7-51.7). After the first transplant, 71 patients (74.7%) experienced bone marrow relapse, 16 patients (16.8%) had extramedullary relapse, 5 patients (5.3%) had both bone marrow and extramedullary relapse and 3/95 patients (3.2%) had positive minimal residual disease (MRD) only. Patients received autologous (n=55, 57.9%) or allogeneic (n=28, 29.5%) CAR-T cells, while 10 patients (10.5%) were unknown, and two (2.1%) received both autologous and allogeneic CAR-T. All patients achieved CR after CAR-T therapy. Before second HSCT, 86 patients (90.5%) were MRD-negative, and 9 (9.5%) were MRD-positive. All second transplant donors were different from the first transplant donors. The median follow-up time was 623 days (range: 33-1901) after the second HSCT. The 3-year overall survival (OS) and leukemia-free survival (LFS) were 55.3% (95%CI, 44.3-66.1%) and 49.8% (95%CI, 38.7-60.9%), respectively. The 3-year relapse incidence (RI) and non-relapse mortality (NRM) were 10.5% (95%CI, 5.6-19.6%) and 43.6% (95%CI, 33.9-56.2%), respectively. In multivariate analysis, the interval from CAR-T to second HSCT ≤90 days was associated with superior LFS(HR, 4.10, 95%CI,1.64-10.24; p=0.003) and OS(HR, 2.67, 95%CI, 1.24-5.74, p=0.012), as well as reduced NRM (HR, 2.45, 95%CI, 1.14-5.24, p=0.021). Conclusions: Our study indicated that CAR-T therapy followed by consolidation second transplant could significantly improve long-term survival in B-ALL patients who relapsed post-transplant. The second transplant should be considered in suitable patients and is recommended to be performed within 90 days after CAR-T treatment.